The Strategy Of Al-Muayyad Islamic Boarding School In Spreading Moderate Understanding Among Santri The Community - Istiqomah, Istiqomah (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2023)
Abstract: Claims related to the existence of a relationship between terrorist networks and Islamic boarding schools have been refuted through various previous studies. Some of the logical reasons put forward in previous research are the need to distinguish between the personal perpetrators of terrorism and the pesantren institution itself, besides that there are not a few studies that show the contribution of pesantren in the development and dissemination of Islamic understanding that is rahmatal lil alamin. This study aims to look at the strategy of the Al-Muayyad Islamic boarding school in Solo in spreading moderate understanding among students and the general public. This study uses qualitative research methods with data collection techniques using interviews, observation and documentation studies. The results showed that the Al-Muayyad Islamic Boarding School in Solo developed based on the thought of the kyai, namely that pesantren should not be an ivory tower in society, but integrated into the community. The strategy for spreading the notion of moderation is in the form of introducing, which is then contained in the form of activities in the form of building interfaith cooperation, using a humanist approach instead of a dogmatic-theological approach in addressing differences, and the establishment of interfaith pesantren. Abstrak: Klaim terkait adanya hubungan antara jaringan teroris dengan pesantren telah terbantahkan melaui berbagai penelitian terdahulu. Beberapa alasan logis yang dikemukakan pada penelitian terdahulu adalah perlunya membedakan antara personal pelaku terorisme dengan institusi pesantren itu sendiri, selain itu tidak sedikit penelitian yang menunjukan kontribusi pesantren dalam pembangunan dan penyebar luasan paham isalm yang rahmatal lil alamin. Penelitian ini bertujuan untuk melihat strategi pondok pesantren Al-Muayyad Solo dalam menyebarkan paham moderat di kalangan santri dan masyarakat umum. Penelitian ini menggunakan metode penelitian kualitatif dengan teknik pengumpulan data menggunakan wawancara, observasi dan studi dokumentasi. Hasil penelitian menunjukan bahwa Pondok Pesantren Al-Muayyad Solo berkembang berdasarakan pemikiran kyai, yaitu pesantren tidak boleh menjadi menara gading di masyarakat, tetapi menyatu dengan masyarakat. Strategi penyebaran paham moderasi berupa memperkenalkan, yang kemudian tertuang dalam bentuk kegiatan berupa membangun kerjasama lintas agama, menggunakan pendekatan humanis bukan teologis-dogmatis dalam menyikapi perbedaan, dan pembentukan pesantren interfaith